Evaluación de la producción de biogás mediante digestión anaerobia a partir de lodos residuales de la PTAR Villas del Nuevo Siglo, en la Mesa-Cundinamarca (2019)
In this research work the production of biogas by anaerobic digestion was evaluated from residual sludge obtained from the WWTP Villas del Nuevo Siglo in the municipality of La Mesa located in the department of Cundinamarca. Initially, a characterization of physicochemical properties of the sludge was performed in order to know the composition of the sludge; obtaining that the organic carbon content is 21,18 % w/v of total nitrogen is 0,012 % w/v and aluminium is 106,87 mg/g. Calculation of the carbon-nitrogen ratio was performed showing that it was necessary to enrich the sludge with a substrate rich in nitrogen, which, in this case, the chicken manure was chosen. As a result of the composition of the chicken manure it was obtained that the organic carbon content is 18,57 % w/v, total nitrogen is 13,67 % w/w. The mixtures were then prepared with a C/N ratio of 20:1 and 30:1, obtaining a volumetric ratio between sludge and chicken manure of 10,157:0,343 and 10,276: 0,224 for a volume of 10,5 L respectively.